“Hybrid One” as Media to Facilitate English Learning in Blended Learning System at SMPN 1 Lamongan - Alvin Failusuf; Nur Afifah; Siska Ayu Putri Utami (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2022)
Hybrid One” is one of the learning management systems which is own by SMPN 1 Lamongan to facilitate students learning process while implementing a blended learning system. This study used a descriptive qualitative design to find how “Hybrid One” works and how the use of “Hybrid One” during the learning process. Researchers used two instruments to find the data, those are Questionnaires which were distributed to seventh-grade students, and interview guidelines which were conducted to 3 English teachers in the school selected. The result of the study showed that “Hybrid One” is an ideal learning management system to be used to support the students’ learning process during this pandemic era. It could be seen from the aspects, they are Implementation, strength, weakness, effectiveness, and application which could work and use appropriately. Although a feature of Hybrid One cannot be used maximally, the others could work maximally during the English learning process